Security Design with Investor Private Information - AXELSON, ULF (Journal of Finance, 2007)
ABSTRACT I study the security design problem of a firm when investors rather than managers have private information about the firm. I find that it is often optimal to issue information‐sensitive securities such as equity. The “folklore proposition of debt” from traditional signaling models only goes through if the firm can vary the face value of debt with investor demand. When the firm has several assets, debt backed by a pool of assets is optimal when the degree of competition among investors is low, while equity backed by individual assets is optimal when competition is high.